Pengaruh Kepercayaan kepada Pemerintah, Tarif Pajak, Kesadaran Wajib Pajak, dan Kebijakan Perpajakan terhadap Kepatuhan Wajib Pajak Orang Pribadi Non Karyawan - Faradila Yuliani; Triana Anggraini (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2026)
Taxes are the main source of state revenue that play an important role in financing development. However, the level of taxpayer compliance, especially individual non-employee taxpayers, is still low and fluctuating. This compliance is influenced by several factors, such as trust in the government, tax rates, taxpayer awareness, and tax policies. This study aims to determine the influence of trust in the government, tax rates, taxpayer awareness, and tax policies on the compliance of non-employee individual taxpayers. The population in this study consists of non-employee individual taxpayers registered at the Primary Tax Office under the South Jakarta II Regional Office of the Directorate General of Taxes. The research sample was determined using a purposive sampling technique, resulting in 96 respondents who met the research criteria. The data used is primary data collected through the distribution questionnaires using a likert scale. This study used a multiple linear regression analysis with the help of IBM SPSS Software version 22. The results of this study indicate that trust in the government has a negative effect on taxpayer compliance, tax rates have a positive effect on taxpayer compliance, taxpayer awareness has no effect on taxpayer compliance, and tax policy has a positive effect on taxpayer compliance.